Case Report: Two Cases of Salivary Duct Carcinoma in Workers With a History of Chromate Exposure - Seçin, Imran; Uijen, Maike J. M.; Driessen, Chantal M. L.; van Herpen, Carla M. L.; Scheepers, Paul T. J. (Frontiers in Medicine, 2021)
Background: Salivary duct carcinoma (SDC), one subtype of the 22 different salivary gland cancers, is a rare malignancy. Risk factors for the development of salivary gland cancer and SDC are largely unknown, although pollution has been described as one of the risk factors. In other cancers, especially in lung cancer, the carcinogenicity of chromium VI (Cr(VI)) is well-known. Here we report on two SDC patients who were occupationally exposed to Cr(VI) and discuss a potential relation between their Cr(VI) exposure and the occurrence of SDC. Case presentation: The work history for two SDC patients was analyzed for chemical exposures. Both patients had a history of Cr(VI) exposure, with maintenance of military equipment considered as the source for this exposure. Inhalation of Cr(VI) containing particles from the removal of old paint by mechanical abrasion was identified as a probable source of exposure for both patients, and one of these patients also applied new paint. Both patients reported not to have used any respiratory protection which may have resulted in substantial inhalation of Cr(VI)-containing chromates. Furthermore, in one patient inhalation of fumes from soldering may have resulted in relevant co-exposure. Conclusion: A causal relation between Cr(VI) exposure and SDC, a rare cancer, cannot be demonstrated on an individual basis but detection in a population-based study is also unlikely because of the extremely low prevalence. Nevertheless, the work history is considered a relevant risk factor in the onset of SDC as occupational exposures to Cr(VI) occurred in poorly ventilated working environment and without using appropriate respiratory protective equipment.